The Interrelationships Between Hybrid Work, Employee Performance and Organizational Culture at the Workplace: A Conceptual Framework - Sharifah Zaanatu Zainab Syed Zakaria; Khairulneezam Mohd Noor; Mashitah Sulaiman (Yayasan Dakwah Islamiah Malaysia (YADIM), 2025)
Non-Indexed Publication